1987
DOI: 10.3109/02688698708999633
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Arterial Vasospasm Following Severe Head Injury: A Transcranial Doppler Study

Abstract: Transcranial Doppler ultrasound was used to determine the natural history of cerebral arterial vascular spasm following severe head injury. Doppler Flow Velocity (DFV) was measured in the anterior cerebral, middle cerebral and terminal carotid arteries. High DFVs consistent with vasospasm were identified in 68% of the 25 patients studied. They came on from between 12 h and 4 days and lasted from 12 h to 14 days. No relationship could be determined between presumed vasospasm and blood pressure, intracranial pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 6 publications
3
49
0
2
Order By: Relevance
“…This would also agree with the findings from Freytag [2]. 405 There are some investigations such as those performed by Compton and Teddy [13], Martin et al [14], Sander and Klingelhofer [15] and Bellner et al [16] whose results signal parallels to aneurysmal SAH. These studies have shown an increase in flow velocities consistent with vaso spasm, with a time course somewhat similar to that seen in aneurysmal vasospasm.…”
Section: Discussionsupporting
confidence: 80%
“…This would also agree with the findings from Freytag [2]. 405 There are some investigations such as those performed by Compton and Teddy [13], Martin et al [14], Sander and Klingelhofer [15] and Bellner et al [16] whose results signal parallels to aneurysmal SAH. These studies have shown an increase in flow velocities consistent with vaso spasm, with a time course somewhat similar to that seen in aneurysmal vasospasm.…”
Section: Discussionsupporting
confidence: 80%
“…Although our sample size was small, the prevalence of CV observed in the present study was similar to that reported from several studies in adult patients with traumatic brain injury. 6,23,30,36 Our study is limited by its retrospective nature. Not every child underwent a TCD examination, and not every DSA finding could be compared with one from a TCD examination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zubkov et al has shown that more clinically mild, post-traumatic vasospasm resembles the morphological features of aneurysmal vasospasm in histopathological studies [54]. Post-traumatic vasospasm may occur earlier than postaneurysmal rupture vasospasm following the ictus, but the duration of the former for 10-12 days is similar to that of the latter [12,20,30,32,38,40,46,53]. Although vasospasm has been shown to occur following traumatic SAH (tSAH), it can be detected in 2-41% of patients with head injury by angiography [30,53] and as high as 60% by TCD [12,20,30,32,38,40,46,53] even in the absence of tSAH [36].…”
Section: Introductionmentioning
confidence: 99%
“…Whether tSAH is an independent causative factor for worse clinical outcome following TBI by deleterious processes such as vasospasm [12,16,27,32,49,53], or merely a marker of more severely incurred head injury [9,34,43] still remains highly debated [4]. Furthermore, assuming tSAH is an independent causative factor for worse clinical outcome, whether its deleterious effects are through ischemic mechanisms secondary to vasospasm as thought to occur in aSAH is still open to speculation [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation